The Symbolic Meaning of “Maccera Ase” Tradition: St Rahma Syam Ali, Selvy Anggriani Syarif, Muhammad Ismail - Selvy Anggriani Syarif; Muhammad Ismail; St Rahma Syam Ali (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2022)
The maccera ase cultural procession has many symbolic meanings. One procession that has been carried out for generations in maccera ase is putting chicken blood in the ball position (the center pole of the house). This study aims to describe the procession and symbolic meaning of the Maccera Ase culture in Sipatuo Village, Patampanua District, Pinrang Regency. conclusion. The results of the study found that the Maccera Ase cultural procession in Sipatuo Village, Patampanua District, Pinrang Regency was carried out after carrying out the rice harvest at the farmer's house as a form of gratitude for the harvest given by Allah SWT. The stages of the Maccera Ase procession go through the stages of planning the time and location of the event, the preparation of goods and materials to be used and the Mabbaca Doang process. The symbolic meaning contained in the Maccera Ase culture is the slaughter of chickens which is meaningful as a form of sacrifice, devotion and protection. the meaning of chicken/manu blood as a hope of family safety and a symbol of the implementation of Maccera Ase in the house. The meaning of serving chicken dishes as a dish with the hope of being given a long life, sokko as a form of request for safety and protection of farmers' crops, young coconuts as a form of fortune that is expected to flow as clear as coconut water, and the meaning of bananas as a form of gratitude and as a form of prayer for good fortune.